Mandate for Leadership: The Conservative Promise By D.Bakst, J.Berry, L. M.Burke, D. R.Burton, A.Candeub, D. J.Carmack, B.Carr, B. S.Carson, P.Sr., Dans, K.Cuccinelli, R.Dearborn, V.deRugy, D.Devine, D.Furchtgott‐Roth, T. F.Gilman, M. M.Gunasekara, G.Hamilton, J.Hazelton, K.Kerrigan, D. D.Kirk, K.Lassman, B. L.McNamee, C.Miller, S.Moore, M.Namdar, P.Navarro, W. P.Pendley, M.Primorac, R.Severino, K. K.Skinner, B. D.Tucker, H. V.von Spakovsky, R.Vought, W. L.Walton, and P.Winfree, Washington DC: The Heritage Foundation. 2023. pp. ix‐887. ISBN: 978‐0‐89‐195174‐2 - Greenstein, Gabriel (Public Administration Review, 2025)
Keywords: Berry; Biology; Botany; Carr; Humanities; Philosophy; dept.psc

Exploring Perceived Fairness in Performance Evaluation Among Telecommuting Employees in Public Agencies - Aggarwal, Jyoti; Hoang, Thanh (Public Administration Quarterly, 2025)
Keywords: Business; Economics; Engineering; Marketing; Political science; Psychology; Public relations; Public sector; Telecommuting; Work (physics); dept.psc; fairness; federal government; organizational justice; performance evaluation; public sector; telecommute

Oral Hygiene Care of Older Adults and Caregiver Education: A Systematic Review - Asanza, Dachel; Njoku, Anuli; Baviskar, Snehal; Evans, Marian; Mouloudj, Kamel (Hygiene, 2025)
Background: There is a need to develop comprehensive guidelines to encourage the promotion of oral hygiene care among older adults and to assist caregivers in this endeavor, taking into consideration the specific challenges that arise from aging, comorbidities and caregiving. Methods: This review was conducted by searching across relevant literature from meta-databases including Academic Google, PubMed, Scielo and Scopus for studies published from 2020 to 2024. PRISMA guidelines were followed. We included articles that described oral hygiene methods, caregiver education and mechanization status of older adults. Common themes, best practices, and gaps in current guidelines were tracked using extracted and analyzed data. Results: The review revealed multiple factors affecting the oral hygiene of older adults, with themes relating to physical impairment, cognitive dysfunction, and caregiver involvement. Highlighted between the approaches are individualized therapy for oral hygiene, caregiver education, and the use of technology to improve adherence to oral hygiene. Barriers like dental care access, underlying medical conditions complicating dental treatments, and cost considerations were identified. Conclusions: The findings emphasize the necessity of clear recommendations that can help caregivers and advance dental care for older adults.
Keywords: Dental care; Hygiene; MEDLINE; Oral health; Oral health care; Oral hygiene; Promotion (chess); Scopus; aged; caregiver education; caregivers; dentistry; dept.pch; education; frail elderly; healthy aging; older adult; oral health; oral hygiene; oral medicine

Period Poverty Among Black, Hispanic and Low-Income Communities in the United States: Challenges and Recommendations - Njoku, Anuli; Alhassan, Mubarak; Tohura, Sharaban; Garcia, Kayla (Hygiene, 2025)
Period poverty refers to the lack of access to or affordability of menstrual hygiene supplies such as sanitary products and the inaccessibility of washing facilities, waste disposal and educational materials. Period poverty can significantly affect menstruating individuals’ physical, mental, and reproductive health and emotional wellbeing; negatively impact educational outcomes; cause financial strain; result in absenteeism from work and school; create barriers to healthcare access; and perpetuate poor health outcomes for generations. Barriers to menstrual equity include lack of access to period support, cost, poor sanitary facilities, lack of education, social and cultural stigma, and legal restrictions. Therefore, it is crucial to actively advocate for initiatives to increase access to menstrual hygiene products, raise public awareness, and educate individuals on safe menstrual practices. Approximately 500 million girls and women worldwide and an estimated 16.9 million people in the United States experience period poverty, with the issue being particularly common among marginalized groups such as Black or Hispanic menstruating individuals and those who are homeless, living in poverty, of low income, or attending college. This article investigates the physical, psychological, educational and social impacts of inequitable access to menstrual products, menstrual education, and sanitation facilities among menstruating individuals who are Black, Hispanic or of low income within the United States. We examine the threat this poses to health equity and propose recommendations to address this pervasive issue.
Keywords: Absenteeism; Equity (law); Health care; Hygiene; Poverty; Public health; Sanitation; Socioeconomic status; dept.pch; environmental sustainability; gender disparities; health equity; menstrual education; menstrual health; menstrual health management; menstrual hygiene products; period poverty; period tax; polycystic ovarian syndrome (PCOS); poverty alleviation; women’s health

Social justice with harm reduction approaches for mothers who use opioids: an international comparative ethnographic study with community engaged methods - Boeri, Miriam; Lamonica, Aukje; Whittaker, Anne; Bruce, Marisa (Harm Reduction Journal, 2025)
BACKGROUND: Mothers and pregnant women who use opioids are particularly vulnerable. Mothers often fear surveillance, stigma, and loss of custody of their children when seeking treatment. Although opioid agonist therapy (OAT) has been shown to be effective, access varies regionally, and not all mothers can cease using opioids. This study compares outcomes of mothers who use opioids in the UK with universal healthcare and OAT access, and mothers in the U.S. with restricted healthcare and OAT access, focusing on their interactions with services. METHODS: This is a secondary data analysis of two studies on mothers who use opioids. Data were collected from nine mothers in Scotland (UK) and 20 mothers in New Jersey (US) through ethnographic, longitudinal studies spanning one year. The UK study used a "Learning Alliance" engagement approach, a patient/public engagement model that involves stakeholders in developing objectives and the dissemination of findings. The US study engaged "community-based consultants," who are paid individuals with lived experience from the study field communities to assist researchers in recruitment and ethnographic fieldwork. Ethical approval was received from review boards. Data were anonymized before analysis, and people with lived experience provided feedback on findings. Grounded theory methods were used for analysis. RESULTS: Findings reveal both convergent and divergent experiences. Mothers in Scotland had more access to healthcare and social housing but faced increased surveillance, while New Jersey mothers often experienced housing insecurity and difficulty obtaining healthcare. Shared challenges included trust issues, stigmatization, inconsistent practitioner engagement, responsibilization, and unclear expectations from child protection services. While Scottish mothers had better access to OAT, both groups faced child custody loss due to unregulated drug use. Mothers in both studies were struggling to meet reunification requirements of abstinence (with or without OAT) within the required time frame. CONCLUSIONS: Differing governance structures create persistent challenges across national boundaries. While health practitioners generally support harm reduction strategies, it does not go beyond OAT for mothers. Our findings indicate the need for radical harm reduction approaches with social justice for mothers who use drugs, including safer parental drug use strategies.
Keywords: Child protection; Community engagement; Corporate governance; Criminal justice; Economic Justice; Ethnography; Harm; Harm reduction; Health psychology; Mothers who use drugs; Opioids; SAFER; Social policy; dept.pch

President Nixon and Senator Kennedy on Health Care: How Rivalry Shaped Reform - Hopper, Jennifer (Congress & the Presidency, 2025)
Keywords: Economics; Health care; Health care reform; Health policy; Law; Law and economics; Political science; Public administration; Rivalry; Sociology; dept.psc; peer-reviewed